Development of a Highly Compact and Robust Chemical Reaction Mechanism for Unsaturated Furan Oxidation in Internal Combustion Engines via a Multiobjective Genetic Algorithm and Generalized Polynomial Chaos - Tay, Kun Lin (AMER CHEMICAL SOC, 2020)
10.1021/acs.energyfuels.9b03272